Does scarcity exacerbate the tragedy of the commons? Evidence from fishers' experimental responses (2009)
Economic Experimental Games (EEGs), focused to analyze dilemmas associated with the use of common pool resources, have shown that individuals make extraction decisions that deviate from the suboptimal Nash equilibrium. However, few studies have analyzed whether these deviations towards the social optimum are affected as the stock of resource changes. Performing EEG with local fishermen, we test the hypothesis that the behavior of participants differs under a situation of abundance versus one of scarcity. Our findings show that under a situation of scarcity, players over-extract a given resource, and thus make decisions above the Nash equilibrium; in doing so, they obtain less profit, mine the others-regarding interest, and exacerbate the tragedy of the commons. This result challenges previous findings from the EEG literature. When individuals face abundance of a given resource, however, they deviate downward from the prediction of individualistic behavior. The phenomenon of private, inefficient over-exploitation is corrected when management strategies are introduced into the game, something that underlines the importance of institutions.